Frictional Properties of Opalinus Clay: Implications for Nuclear Waste Storage. Issue 1 (12th January 2018) - Orellana, L. F.; Scuderi, M. M.; Collettini, C.; Violay, M.
Abstract: The kaolinite‐bearing Opalinus Clay (OPA) is the host rock proposed in Switzerland for disposal of radioactive waste. However, the presence of tectonic faults intersecting the OPA formation put the long‐term safety performance of the underground repository into question due to the possibility of earthquakes triggered by fault instability. In this paper, we study the frictional properties of the OPA shale. To do that, we have carried out biaxial direct shear experiments under conditions typical of nuclear waste storage. We have performed velocity steps (1–300 μm/s) and slide‐hold‐slide tests (1–3, 000 s) on simulated fault gouge at different normal stresses (4–30 MPa). To establish the deformation mechanisms, we have analyzed the microstructures of the sheared samples through scanning electron microscopy. Our results show that peak ( μ peak ) and steady state friction ( μ ss ) range from 0.21 to 0.52 and 0.14 to 0.39, respectively, thus suggesting that OPA fault gouges are weak. The velocity dependence of friction indicates a velocity strengthening regime, with the friction rate parameter ( a  −  b ) that decreases with normal stress. Finally, the zero healing values imply a lack of restrengthening during interseismic periods. Taken together, if OPA fault reactivates, our experimental evidence favors an aseismic slip behavior, making the nucleation of earthquakes difficult, and long‐term weakness, resulting in stable fault creeping over geological times. Based on the results, our study confirms the seismic safety of the OPA formation for a nuclear waste repository. Key Points: Laboratory study on the frictional properties of Opalinus Clay, a host rock for nuclear waste storage, was presented Faults within the Opalinus Clay formation are mechanically weak Velocity strengthening and lack of restrengthening during interseismic periods predict aseismic fault slip behavior